Seagrass recovery after fish farm relocation in the eastern Mediterranean. (September 2018) - Kletou, Demetris; Kleitou, Periklis; Savva, Ioannis; Attrill, Martin J.; Antoniou, Charalampos; Hall-Spencer, Jason M.
Abstract: Finfish aquaculture has damaged seagrass meadows worldwide as wastes from the farms can kill these habitat-forming plants. In Cyprus, the Mediterranean endemic Posidonia oceanica is at its upper thermal limits yet forms extensive meadows all around the island. Understanding this under-studied isolated population may be important for the long-term survival of the species given that the region is warming rapidly. When fish farming began around Cyprus in the mid-nineties, cages were moored above seagrass beds, but as production expanded they were moved into deeper water further away from the meadows. Here, we monitored the deepest edge of meadows near fish farms that had been moved into deeper waters as well as at a decommissioned farm site. Four P. oceanica monitoring systems were set up using methods developed by the Posidonia Monitoring Network. Seagrass % coverage, shoot density, % of plagiotropic rhizomes, shoot exposure, leaf morphometry, and sediment organic matter content and grain size were monitored at 11 fixed plots within each system, in 2012–2014 and in 2017. Expansion at the lower depth limit of seagrass meadows was recorded at all monitoring sites. Most other P. oceanica descriptors either did not change significantly or declined. Declines were most pronounced at a site that was far from mariculture activities but close to other anthropogenic pressures. The most important predictor affecting P. oceanica was depth. Monitoring using fixed plots allowed direct comparisons of descriptors over time, removes patchiness and intra-meadow variability increasing our understanding of seagrass dynamics and ecosystem integrity. It seems that moving fish farms away from P. oceanica has helped ensure meadow recovery at the deepest margins of their distribution, an important success story given that these meadows are at the upper thermal limits of the species. Highlights: Around Cyprus, fish farming expanded rapidly but cages moved away from the seagrass beds to mitigate impacts. Four seagrass monitoring systems were set up near fish farms and decommissioned sites. Data collection was repeated from the same fixed-plots about five years later. Progression of seagrass beds was noted and present-day farms in deep water, are not preventing nearby seagrass growth.